Influence of the extraction–purification conditions on final properties of alginates obtained from brown algae (Macrocystis pyrifera) - Gomez, Cesar Gerardo (2009)
In this work, three methods (ethanol, HCl, and CaCl2 routes) of sodium alginate extraction–purification from brown seaweeds (Macrocystis pyrifera) were used in order to study the influence of process conditions on final properties of the polymer. In the CaCl2 route, was found that the precipitation step in presence of calcium ions followed by proton-exchange in acid medium clearly gives alginates with the lowest molecular weight and poor mechanical properties. It is well known that the acid treatment degrade the ether bonds on the polymeric chain. Ethanol route displayed the best performance, where the highest yield and rheological properties were attained with the lowest number of steps. Although the polymer I.1 showed a molar mass and polydispersity index (Mw/Mn) similar to those of commercial sample, its mechanical properties were lower. This performance is related to the higher content of guluronic acid in the commercial alginate, which promotes amore successful calcium chelation.Moreover, the employment of pH 4 in the acid pre-treatment improved the yield of the ethanol route, avoiding the ether linkage hydrolysis. Therefore, samples I.2 and I.3 displayed a higher Mw and a narrower distribution of molecular weights than commercial sample, which gave a higher viscosity and better viscoelastic properties.